TOBAT DALAM PERSPEKTIF ALQURAN - Sadik, Moh. (Hunafa: Jurnal Studia Islamika, 2010)
This article deals with repent in the perspective of the Qur’an. The word taubah and the root words of it was found 85 times in the Qur’an with its derivations. Taubah means returning to God with obedience and commitment not to commit the offences forbidden by God. Taubah will be performed after a man or a woman has committed the offences and sins. In addition, taubah is performed as an obligation and medium to approach God as a realization of one’s faith in God.